(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The impact of aggressive agents, especially chlorides, on concrete structures is a significant challenge in the field of engineering. The presence of chlorides leads to corrosion and deterioration of concrete, affecting its performance. Chlorides penetrate the concrete, leading to the destruction of the protective layer around the reinforcing steel, which results in the corrosion of the steel and the formation of rust. This corrosion negatively affects the bond strength between the steel and the concrete and can also cause cracks on the concrete surface, reducing its durability. To address this challenge, a research study was conducted to explore the use of nanomaterials, specifically nano-calcined halloysite, to improve the performance and durability of concrete. The aim was to investigate the impact of incorporating halloysite in concrete on the penetration of chlorides and the subsequent corrosion of reinforcing steel rebars. Three different concrete mixtures containing varying percentages of halloysite (1.5%, 3%, and 4.5%) were examined. The researchers evaluated the water absorption rates and migration coefficients of these mixtures. Additionally, the impressed current technique was utilized, where a 14mA current was applied for 26 days to accelerate the corrosion of steel rebars. The results of the study demonstrated the effectiveness of incorporating halloysite in concrete to enhance its properties. The mixture containing 3% and 4.5% of halloysite (CHNC) achieved the desired objectives, significantly reducing water absorption. For example, the mixture with 4.5% CHNC showed a 42.99% reduction in water absorption after 7 days. This decrease in water absorption also led to a considerable decrease in the migration coefficient of chlorides and their penetration in the concrete. Furthermore, the inclusion of 4.5% halloysite and 25% ground granulated blast furnace slag (GGBS) in the mixture further improved its performance.